Methodological approaches to study antibody aggregation and thermal stability - Poikonen, Suvituuli (My University, 2022)
Therapeutic monoclonal antibodies are alluring novel drug candidates for the treatment of various diseases, but their complicated structures also present challenges in meeting the stability requirements of drugs. The utility of external luminescent probes in the detection of protein aggregates compared to common methods of SEC-MALS and DLS used in the pharmaceutical industry was assessed in this study. The methods were compared in terms of sensitivity, specificity towards different aggregates, and overall performance. Also, the applicability of different (nano)DSF methods was compared in producing thermal unfolding curves of the chosen antibodies. Luminescent probes proved their applicability and high sensitivity in aggregation studies while problems with the more established light scattering-based methods surfaced. The probes were able to produce quantitative results for the samples, while SEC-MALS detected aggregation primarily as reduced content of the intact protein. DLS produced qualitative results but suffered from low resolution. Multiple analytical methods are still required to confirm the results from aggregate studies due to the dynamic and complicated nature of aggregates. In the thermal unfolding experiments, nanoDSF reliably produced unfolding curves for all the studied mAbs without external components. The external probes had more variance between different mAbs, which was reflected in the unfolding curves. However, the lowest LLD was achieved with a FRET-probe that utilizes the long lifetime of Eu3+-chelate emission.
Keywords: aggregation, antibody, DLS, external probes, light scattering, luminescence, MALS, size-exclusion chromatography, thermal unfolding